Factors Associated with Visit to Posyandu Toddlers in the work area of the Public Health Center Gogagoman: Faktor-faktor yang Berhubungan dengan Kunjungan Posyandu Balita di Wilayah Kerja Puskesmas Gogagoman - Strahmawati Hamzah (Journal of sciences and health, 2022)
Background: The coverage rate of toddlers visits at posyandu has not been able to meet the target set by the government, which is 90%. The government, in this case the Ministry of Health, has strengthened the posyandu to become a forum for the community to maintain the health of infants and toddlers. In fact, complete visits to the Posyandu for toddlers are still lacking because they are influenced by low knowledge about the benefits of Posyandu, the number of children and the mother's employment status. The purpose of this study was to determine the factors associated with visit to the Posyandu for toddlers (1-5 years) in the work area of the Public Health Center Gogagoman. Method: The type of research used is analytic observational with a cross sectional study design. The sample in this study was 94 respondents, obtained by simple random sampling technique. Data were collected using a questionnaire and analyzed by univariate and bivariate with chi square test. Results: The results showed that there was a relationship between the level of knowledge (19,03>2,706), parity (11,95>2,706), and job status (10,07>2,706) with visit to the Posyandu for toddlers (1-5 years) in the work area of the Public Health Center Gogagoman. The participation of mothers under five in visiting posyandu can be influenced by knowledge about the benefits of posyandu and the time it takes to take care of children and working. Conclusions: Factors related to visit to the Posyandu for toddlers (1-5 years in the work area of the Public Health Center Gogagoman are the level of knowledge, parity, and job status. Keywords: Knowledge, parity, job, posyandu, toddler